A kaempferol triglycoside from Tephrosia preussii Taub. (Fabaceae). Issue 21 (2nd November 2017) - Mba Nguekeu, Yves Martial; Awouafack, Maurice Ducret; Tane, Pierre; Nguedia Lando, Marius Roch; Kodama, Takeshi; Morita, Hiroyuki
Abstract: A phytochemical investigation of the MeOH extract of twigs and leaves of Tephrosia preussi was carried out to give a new kaempferol triglycoside, named tephrokaempferoside (1 ), together with five known compounds: tephrosin (2 ), betulinic acid (3 ), lupeol (4 ), β -sitosterol (5 ) and 3- O - β -d -glucopyranoside of β -sitosterol (6 ). The structure of the new compound was characterised by analyses of NMR (1D and 2D) and MS data, and chemical conversion. Tephrokaempferoside (1 ) had weak antibacterial activity against Klebsiella pneumoniae with an MIC value of 150 μg/mL. Abstract :